If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3p + 9q + -7(2p + -8q) = 0 3p + 9q + (2p * -7 + -8q * -7) = 0 3p + 9q + (-14p + 56q) = 0 Reorder the terms: 3p + -14p + 9q + 56q = 0 Combine like terms: 3p + -14p = -11p -11p + 9q + 56q = 0 Combine like terms: 9q + 56q = 65q -11p + 65q = 0 Solving -11p + 65q = 0 Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '-65q' to each side of the equation. -11p + 65q + -65q = 0 + -65q Combine like terms: 65q + -65q = 0 -11p + 0 = 0 + -65q -11p = 0 + -65q Remove the zero: -11p = -65q Divide each side by '-11'. p = 5.909090909q Simplifying p = 5.909090909q
| 1(4x+2y)=1(-22) | | 3(y-9)=2(5+y) | | 2x+3xy-1=0 | | 5(1+4x)=5-4x | | 14z+122=-676 | | 9(n-1)-(-6n-8)=14n | | 40h-[24-(6h+8)-(5-2h)]=3-8h-12 | | 4*16/8+8+5-1+4 | | 0.13-0.02(x+1)=-0.03(3-x) | | -6a+42=10a+35 | | 22-13x=9 | | 6x+4-5x=0 | | 5y-23=-25+3y | | 250.00(h+15.00)=412.50 | | -9(-6+x)=-63 | | -6x^5+6x^4-2x^3=0 | | 165g=75 | | 11xy+2x=2 | | 250(h+15)=412.50 | | 85=21+4xs | | -3(3.3+8.9r)=6.1-24.7r | | n/15=1 | | (1-x)100=0.25 | | -4v/7=-20 | | 3(b+5y)=2(-5+4y) | | 5y-29=-31+4y | | 2(x-3)+7=10 | | (5/1)-(2(3a-4)/5)=(7-2a/2) | | -9c+1=-35 | | -7+36/-9x-1 | | 2x^3+5x+2=0 | | 4d-1=-4+4d+3 |